Determinants of Noncompliance to Clinic Appointments and Medications among Nigerian Children with Epilepsy: Experience in a Tertiary Health Facility in Enugu, Nigeria - Roland Chidi Ibekwe; Appolos Chidi Ndukuba; Ann Ebele Aronu; Christopher Bismarck Eke; MaryAnn Ugochi Ibekwe; Ngozi Chinyelu Ojinnaka (Behavioural Neurology)
Purpose. To determine the frequency and determinants of noncompliance to clinic appointment and medication among Nigerian children with epilepsy. Method. This is a cross-sectional survey of noncompliance to clinic appointments and medication among 113 consecutive children with epilepsy attending the Paediatric Neurology Clinic of University of Nigeria Teaching Hospital, Enugu, southeastern Nigeria. Results. Noncompliance to clinic appointment and medication was 23% and 15.3%, respectively. The major reasons given were lack of finance, clashing with school time, and forgetting to take the drugs. Children whose mothers were less educated and unemployed were more likely to miss clinic appointments. Noncompliance to medication was associated with poor seizure control. Children that were on phenobarbitone were more likely to be noncompliant with medication than those on sodium valproate and/or carbamazepine. Conclusion. Missed clinic appointment and medication noncompliance are common among Nigerian children with epilepsy and financial constraint is the most common reason.